The Role of the Leadership in Successful Implementation of the Projects - Irina Andreea PEGULESCU; Ana-Maria PREDILA; Denisa Maria COJOACA (Communications of International Proceedings, 2021)
A better perspective on a successful project is offered through a structured approach when the achievement of objectives is constantly monitored, in collaboration with the use of resources, at the center of all these aspects being the project leader. Thus, the project leader develops an internal control system, which is a process of improving the performance of his project team, being a control system designed to support project implementation, efficient management of operations to achieve project objectives, management of its activities, through more efficient methods at each level of the project. The project leader must find the best way to improve the current systems as the project approach in stages is a methodology that leads to uniformity in project planning, thus benefiting from the use of control at each stage in the development of projects. The findings, the achievements of each stage help the leader to decide on how to continue, this being a permanent and complex process, followed by corrective measures to remove deviations. Following the way of carrying out the tasks leads to the discovery of the possibilities to improve the results, often having restrictions on the coverage time and costs.
Keywords: Leader; project; project team; risks.